(untitled) (Revista Electrónica Calidad en la Educación Superior, 2018)
The multidisciplinary Hackathon academic activity was applied to some groups of mathematics in Universidad Técnica Particular de Loja students during the period time of in October 2016 - March 2017. The students registered worked in multidisciplinary groups to try to response: What problem or social necessity has been detected and how do you resolve? The academic activity was develop in three phases, informative, assay and evaluation. The application of design thinking methodology allow to porpoise the solution in different challenges in environment, food, technologic and educative. A commission stablished evaluated according to a rubric the best project. The results show that the students know and applies the new learning methodologies to learn and apply in future project in science, medicine, education and biotechnology. Keywords: